0
$\begingroup$

Have no idea where to go. A friend suggested taking the difference of Gauss sums, not sure what that means:

$$\sum_{i = 1}^{n}\sum_{j = i}^{2i}j$$

$\endgroup$
0
$\begingroup$

HINT

Recall that $s(n) = \sum_{k=1}^n k = n(n+1)/2$ and note that $$\sum_{j=i}^{2i}j = \sum_{j=1}^{2i} j - \sum_{j=1}^{i-1} j = s(2i) - s(i-1) $$

$\endgroup$
  • $\begingroup$ Why can you break it apart like that? May I have a further explanation? $\endgroup$ – user7252850 Sep 8 '17 at 0:57
  • $\begingroup$ @user7252850 you add and subtract the terms from 1 to $i-1$ (i.e. $s(i-1)$) and the result is all terms from 1 to $2i$... $\endgroup$ – gt6989b Sep 8 '17 at 1:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.